Metal‐Free Cycloaddition of Internal Alkynes and Multifunctional Azides Under Solvent‐Free Conditions. Issue 17 (8th July 2014) - Sandmann, Benedict; Happ, Bobby; Vitz, Jürgen; Paulus, Renzo M.; Hager, Martin D.; Burtscher, Peter; Moszner, Norbert; Schubert, U. S.
<x xml:space="preserve">Abstract</x> The synthesis of three different electron‐deficient internal alkynes for the metal‐free 1, 3‐dipolar azide–alkyne cycloaddition is shown. The alkynes are polymerized with several multifunctional azides and the reaction enthalpy (ΔH) is investigated by differential scanning calorimetry (DSC). The mechanical properties of the resulting polymers are analyzed using nanoindentation. The polymerization results in hard materials with an E‐modulus of maximum 2.5 GPa, which make them interesting in particular for biomedical applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>